CSF oligoclonal bands in neurological diseases besides CNS inflammatory demyelinating disorders - Feng Gao; Jing Guo; Ran Liu; Yan Yao; Jingru Ren; Jianchun Wang; Hongjun Hao (BMJ Neurology Open)
Objective To understand the distribution characteristics and clinical significance of cerebrospinal fluid (CSF) oligoclonal bands (OCBs) in different nervous system diseases besides typical central nervous system (CNS) inflammatory demyelinating disorders.Material A total of 2259 patients who underwent CSF examination for OCBs at Peking University First Hospital from January 2011 to December 2023 were tested. A cohort of 257 patients presenting with various types of OCBs but without CNS inflammatory demyelinating diseases was included in the analysis. Relevant medical history was collected from all patients.Results OCBs were most common in patients with autoimmune encephalitis. OCB types II and III were most common in patients with autoimmune encephalitis and CNS infection, whereas OCB types IV and V were present in immune-mediated neuropathy mostly. The distribution of OCBs also varied among different disease subtypes. Other CSF characteristics varied between diseases with different OCBs.Conclusions In addition to CNS inflammatory demyelinating diseases, OCBs also appear in other neurological diseases including cerebral angiopathy and neurodegenerative conditions, informing the potential immune background. Further research is still needed to determine the significance of OCBs in these diseases.